Diversity of Sarcophagidae (Insecta, Diptera) associated with decomposing carcasses in a rural area of the State of Minas Gerais, Brazil - Paseto, Maria Lígia; de Faria, Lucas Silva; Mendes, Júlio; Linhares, Arício Xavier (EntomoBrasilis, 2019)
Abstract. Cerrado biome presents high biodiversity, but it still lacks works that focus on entomological inventories. New records for species of Sarcophagidae were provided, including the first record of Blaesoxipha (Acridiophaga) caridei (Brèthes) to Brazil, and new occurrences of the following species for the Cerrado and/or for the state of Minas Gerais, Brazil: Blaesoxipha (Acanthodotheca) acridiophagoides (Lopes & Downs), Oxysarcodexia mineirensis Souza & Paseto, Oxysarcodexia occulta Lopes, Nephochaetopteryx orbitalis (Curran & Walley), Ravinia effrenata (Walker) and Sarcophaga (Neobellieria) polistensis (Hall). These flies are necrophagous and lay first instar larvae directly on the substrate for feeding and development. Pig carcasses were used as animal model for monitoring the decaying process and attractiveness to insects. This study aimed to evaluate the diversity and abundance of adult Sarcophagidae collected from eight pig carcasses exposed in two different environments at a rural area, and to identify which species used the carcasses as rearing substrates for the immatures. The experiment was carried out until the end of the carcasses decomposition, and lasted 49 days during the dry and cool season (2012), and 30 days during the wet and warm season (2013). A total of 44,446 adults of Sarcophagidae, belonging to 12 genera, 46 species and two morphotypes were collected, mostly during the decay stage of decomposition. In addition, 389 adults of Sarcophagidae emerged from the immatures collected from the carcasses. The present study demonstrated the high diversity of Sarcophagidae attracted by pig carcasses and the high ecological relevance to develop similar studies in other Cerrado areas. Diversidade de Sarcophagidae (Insecta, Diptera) associada à decomposição de carcaças em uma área rural do Estado de Minas Gerais, Brasil Resumo. O bioma Cerrado apresenta grande biodiversidade, mas trabalhos sobre levantamento entomológico ainda são escassos. Novos registros de espécies de Sarcophagidae foram relatados, incluindo o registro inédito de Blaesoxipha (Acridiophaga) caridei (Brèthes) para o Brasil e novas ocorrências das seguintes espécies para o Cerrado e/ou para o estado de Minas Gerais, Brasil: Blaesoxipha (Acanthodotheca) acridiophagoides (Lopes & Downs), Oxysarcodexia mineirensis Souza & Paseto, Oxysarcodexia occulta Lopes, Nephochaetopteryx orbitalis (Curran & Walley), Ravinia effrenata (Walker) e Sarcophaga (Neobellieria) polistensis (Hall). Essas moscas são necrófagas e depositam suas larvas de primeiro instar diretamente sobre o substrato para alimentação e desenvolvimento. Carcaças suínas foram utilizadas como modelo animal para monitorar o processo de decomposição e atratividade de insetos. Este estudo teve como objetivo avaliar a diversidade e abundância de sarcofagídeos adultos coletados em oito carcaças suínas expostas em dois diferentes ambientes de uma área rural, e identificar qual espécie utilizou a carcaça como substrato para criação dos imaturos. O experimento foi encerrado quando as carcaças atingiram o último estágio de decomposição, totalizando 49 dias durante a estação fria e seca (2012) e 30 dias durante a estação quente e úmida (2013). Um total de 44.446 sarcofagídeos adultos, pertencentes a 12 gêneros, 46 espécies e dois morfotipos, foi coletado, principalmente durante o estágio seco do processo de decomposição. Além disso, 389 sarcofagídeos adultos emergiram dos imaturos coletados nas carcaças. O presente estudo demonstrou a grande diversidade de Sarcophagidae atraídos por carcaças suínas e a relevância ecológica de desenvolver estudos similares em outras áreas do Cerrado.